The Effectiveness of the Use of Canva Media on Indonesian Language Learning Outcomes for Grade VII Students SMP Negeri 2 Rappang - Haslinda Mansyur; Usman M; Suardi Zain (MultiTech Publisher, 2024)
This research aims to determine the effectiveness of using Canva media on Indonesian language learning outcomes for Class VII students at SMP Negeri 2 Rappang. This research uses a one group pretest-posttest design and a quasi-experimental research design. The population in this study was class VII.c of SMP Negeri 2 Rappang, totaling 65 students, while the sample in this study was class VII.c of SMP Negeri 2 Rappang, totaling 19 students. The data collection technique used is a test in the form of multiplechoice questions to measure student learning outcomes in terms of complete learning and timeliness in receiving material. The results of this research show that there is effectiveness in using Canva media on the Indonesian language learning outcomes of class VII students at SMP Negeri 2 Rappang. This is shown from the results of the T-test sample test, the pretest and posttest data on student learning outcomes obtained significance values. From the results of this research which have been analyzed, the average value obtained is Mx (Posttest) = 89,8 > My (Pretest) = 63,3. So it can be concluded that this research shows the effectiveness of using Canva media on student learning outcomes.